Outcomes of Hall Technique and Conventional Stainless Steel Crowns in Primary Molars Caries Management: A Scoping Review - Rima Fidayani Rizki; Willyanti Soewondo; Jamas Ari Anggraini (International Journal Labs, 2026)
Stainless steel crowns (SSC) are widely used in the management of carious primary molars. The Hall Technique (HT) has emerged as a minimally invasive alternative that avoids local anesthesia and caries removal. However, evidence regarding the outcomes of HT compared to conventional SSC (CSSC) placement remains varied. This scoping review aims to map the available evidence on the clinical, radiographic, and patient-related outcomes of the Hall Technique and conventional stainless steel crowns in the management of carious primary molars. A scoping review was conducted following the PRISMA-ScR guidelines using the Population–Concept–Context (PCC) framework. Electronic searches were performed in PubMed, Scopus, and EBSCOhost for articles published between 2014 and 2024. Studies reporting outcomes of HT and/or conventional SSCs (CSSCs) in primary molars were included. Data were charted and synthesized descriptively. Seven studies met the inclusion criteria, comprising randomized controlled trials and observational studies conducted in various clinical settings. The included studies reported favorable clinical and radiographic outcomes for both HT and conventional SSC (CSSC), with variations in follow-up duration, outcome measures, and study design. Patient-related outcomes such as discomfort and acceptability were inconsistently reported. The available evidence indicates that both the Hall Technique and conventional stainless steel crowns demonstrate favorable outcomes in managing carious primary molars. However, heterogeneity in study designs and outcome measures highlights the need for further research with standardized reporting and longer follow-up periods.